2022
DOI: 10.1371/journal.pone.0271984
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient intake inadequacy and its associated factors among lactating women in Bahir Dar city, Northwest Ethiopia, 2021

Abstract: Background Inadequate intake of micronutrients in lactating women was prevalent worldwide. In particular, to our knowledge, there has been little report concerning Ethiopian lactating women regarding their micronutrient intake. Our objective was to assess micronutrient intake inadequacy and its associated factors among lactating women in Bahir Dar city, Northwest Ethiopia, 2021. Methods Community-based cross-sectional study was conducted from February 15 to March 05, 2021. Four hundred thirteen respondents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
5

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 28 publications
(51 reference statements)
5
9
5
Order By: Relevance
“…It was observed that the MAR was between 0.29 and 0.94, and none of the lactating mothers met the RDA for all the micronutrients except for iron, which is consistent with the reports of other studies in Ethiopia and Zambia ( 11 , 14 ). This study also revealed that the overall prevalence of micronutrient intake inadequacy (MAR <0.75) among lactating mothers was 72.3%.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…It was observed that the MAR was between 0.29 and 0.94, and none of the lactating mothers met the RDA for all the micronutrients except for iron, which is consistent with the reports of other studies in Ethiopia and Zambia ( 11 , 14 ). This study also revealed that the overall prevalence of micronutrient intake inadequacy (MAR <0.75) among lactating mothers was 72.3%.…”
Section: Discussionsupporting
confidence: 91%
“…This study also revealed that the overall prevalence of micronutrient intake inadequacy (MAR <0.75) among lactating mothers was 72.3%. This is much higher than the findings of the study, which were in Bahir Dar City, Ethiopia ( 14 ) and in rural areas of Indonesia ( 41 ). This high prevalence of micronutrient intake inadequacy can be explained by factors such as excessive cereal consumption (teff, maize, sorghum, etc.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations